Respiratory function and respiratory complications in spinal cord injury: protocol for a prospective, multicentre cohort study in high-income countries - David J Berlowitz; Maria T E Hopman; Martin Schubert; Gabi Mueller; Martin W G Brinkhof; Xavier Jordan; Anja M Raab; Karin Postma; David Gobets; Sven Hirschfeld; Burkhart Huber; Margret Hund-Georgiadis; et al. (BMJ Open)
Introduction Pneumonia is one of the leading complications and causes of death after a spinal cord injury (SCI). After a cervical or thoracic lesion, impairment of the respiratory muscles decreases respiratory function, which increases the risk of respiratory complications. Pneumonia substantially reduces patient’s quality of life, may prolong inpatient rehabilitation time, increase healthcare costs or at worse, lead to early death. Respiratory function and coughing can be improved through various interventions after SCI, but the available evidence as to which aspect of respiratory care should be optimised is inconclusive. Furthermore, ability of respiratory function parameters to predict pneumonia risk is insufficiently established. This paper details the protocol for a large-scale, multicentre research project that aims to evaluate the ability of parameters of respiratory function to predict and understand variation in inpatient risk of pneumonia in SCI.Methods and analysis RESCOM, a prospective cohort study, began recruitment in October 2016 across 10 SCI rehabilitation centres from Australia, Austria, Germany, the Netherlands and Switzerland. Inpatients with acute SCI, with complete or incomplete cervical or thoracic lesions, 18 years or older and not/no more dependent on 24-hour mechanical ventilation within the first 3 months after injury are eligible for inclusion. The target sample size is 500 participants. The primary outcome is an occurrence of pneumonia; secondary outcomes include pneumonia-related mortality and quality of life. We will use the longitudinal data for prognostic models on inpatient pneumonia risk factors.Ethics and dissemination The study has been reviewed and approved by all local ethics committees of all participating centres. Study results will be disseminated to the scientific community through peer-reviewed journals and conference presentations, to the SCI community, other stakeholders and via social media, newsletters and engagement activities.Trial registration details ClinicalTrials.gov NCT02891096.